Upaya Meningkatkan Kreativitas Siswa Melalui Proyek Media Berbasis Canva Pada Mata Pelajaran Informatika SMP Negeri 7 Kota Pontianak - Sarinda, Nurlita Sarinda; Permana, Ryan; Sabirin, Febrianto (Jurnal Inovasi Pendidikan dan Pengajaran (JIPP), 2026)
This classroom action research (CAR) aimed to improve the creativity of eighth-grade students (Class VIII A) at SMP Negeri 7 Kota Pontianak in the Informatics subject through a Canva-based media project using the Project Based Learning (PjBL) model, with the Define, Design, Develop, and Disseminate (4D) framework embedded in the acting phase. This collaborative CAR followed the Kemmis and McTaggart spiral model across two cycles, each consisting of planning, acting, observing, and reflecting stages. The subjects were 38 students, and data were collected through observation sheets and portfolio assessment rubrics covering five creativity indicators: fluency, flexibility, originality, elaboration, and independence, which were analyzed descriptively using mean scores and percentage distributions. The results showed a consistent improvement in students' creativity: the mean score increased from 58.09 in the pre-cycle to 74.41 in Cycle I, with 52.63% of students reaching the "good" or "very good" category, and further increased to 94.11 in Cycle II, with 100% of students reaching the "very good" category, exceeding the 75% success threshold. This improvement occurred progressively across the four PjBL stages, supported by structured idea forms, silent brainstorming, round robin, peer assessment, and role interdependence techniques introduced in Cycle II. These findings indicate that a Canva-based media project within a PjBL framework effectively enhances students' creativity in Informatics learning, particularly in generating original ideas, developing flexible designs, and presenting projects confidently and independently.